Sensory acceptance and biological implications of volatile compounds in Mexican soybean germplasm - Mónica López-Fernández; Octelina Castillo-Ruíz; Benjamín Abraham Ayil-Gutiérrez; Homar Rene Gill-Langarica (Archivos Latinoamericanos de Nutrición)
Introduction: The growing demand for healthy foods has increased interest in soybean products due to their high protein content and bioactive compounds. However, consumer acceptance of these products is limited by undesirable flavors, largely attributed to lipoxygenase activity. Objective: Identify the volatile compounds responsible for off-flavors in beverages derived from Mexican soybean germplasm and analyze their impact on both sensory attributes and the plant’s biological characteristics. Materials and methods: Beverages from eleven Mexican soybean varieties with normal lipoxygenase activity, two Japanese lipoxygenase-free materials, and one commercial beverage were evaluated. Sensory tests were conducted with untrained panelists, and volatile compounds were identified through gas chromatography. Results: Sensory analysis revealed significant differences in taste, appearance, and overall acceptance. Huasteca 200, though not lipoxygenase-free, stood out for its high sensory acceptance. Gas chromatography revealed variations in volatile compounds, such as hexanal and 1-octen-3- ol, associated with bitter flavors and biological traits like pest resistance. Conclusions: Huasteca 200 proved to be a promising variety for genetic improvement programs due to its favorable sensory profile. Volatile compounds such as hexanal and 1-octen-3-ol play a critical role in flavor perception and reflect important biological aspects. These findings underscore the potential of genetic selection to optimize both sensory quality and biological resistance in future Mexican soybean varieties.